ANALYSIS OF THE PSYCHOPATHOLOGICAL AND NEUROPHYSIOLOGICAL PROFILE OF CHILDREN LEFT WITHOUT PARENTAL CARE - Turayev Bobir Temirpulotovich , Ibragimova Muazam Holdorovna (Journal of Science in Medicine and Life, 2024)
In our country, the mental health of children and adolescents deserves special attention. Social orphans represent a separate category. Children in this category are considered the most vulnerable to mental disorders. The main psychopathological disorders of social orphans are depression, suicide, anxiety, aggression, mental retardation, cognitive impairment, and Addiction Disorder.